PEMETAAN KONTRAKTIF LEMAH MULTIVALUED DI RUANG METRIK PARSIAL - Sagita Charolina Sihombing; Ety Septiati (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2017)
In this paper, we study the existence of fixed point of the φ-weak contraction mapping in the complete partial metric space for multivalued mapping. Distance calculations are performed using Hausdorff metric. The result obtained in this paper is an extension of similar result for single valued mapping.